DIFFERENCES IN SEBORRHOEIC DERMATITIS AREA SEVERITY INDEX IN IMMUNOCOMPROMISED AND NON IMMUNOCOMPROMISED PATIENTS - Rossa Amanda, Theresia Dellia; Anggowarsito, Jose L.; Tanudjaja, George Nicolaus (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
Background: Seborrhoeic Dermatitis (DS) is a papulosquamous skin disorder with a predilection for areas rich in sebaceous glands, scalp, face and body. Seborrheic dermatitis in immunocompromised patients is clinically different from non-immunocompromised seborrheic dermatitis patients. Seborrheic dermatitis is one of the clinical symptoms and is most often found in immunocompromised patients such as individuals who have HIV/AIDS compared to seborrheic dermatitis patients in general.Objective: To determine the difference in seborrhoeic dermatitis area severity index in immunocompromised and non-immunocompromised patients.Method: This research design uses analytical observational with a cross sectional approach. The population of seborrheic dermatitis patients was 70 people with 35 immunocompromised patient respondents and 35 non-immunocompromised respondents. Data collection starts from September 22 to October 26 2023. Seborrheic dermatitis examination is carried out on the face and scalp by comparing the area affected by seborrheic dermatitis with the surrounding area and then assessing the degree of the area affected by seborrheic dermatitis using SDASI. The assessment of the area of the lesion is multiplied by the sum of the erythema, scale and papule scores with a severity classification, namely: Mild: 0-7.9, Moderate: 8-15.9, Severe: >16. The results of the examination will be recorded and a score for the severity of seborrheic dermatitis on the face and scalp will be calculated.Results: Seborrhoeic dermatitis in 35 immunocompromised respondents and 35 non-immunocompromised respondents. The results obtained from the seborrheic dermatitis patient group were immunocompromised patients, namely 14 respondents with mild degrees (40.0%), 17 respondents with moderate degrees (48.6%), and four respondents with severe degrees (11.4%) while in the group of non-immunocompromised patients there were 20 respondents with mild degrees. (57.1%), 11 respondents had a moderate degree (31.4%), and four respondents had a mild degree (11.4%). The results of research analysis using the independent T-test showed that there was a difference in SDASI in immunocompromised and non-immunocompromised patients with a value of p = 0.040 (p < 0.05).Conclusion: there are differences in SDASI in immunocompromised and non-immunocompromised patients.